PENERAPAN VISI SEKOLAH MANTAP (MANDIRI, AKHLAK MULIA, NASIONALIS, TANGGUH, PEDULI ) SEBAGAI UPAYA MEWUJUDKAN MURID BERPROFIL PELAJAR PANCASILA DI SEKOLAH DASAR - Leny Vitriasari; Dinn Wahyudin; Roni Wahyu Wandani (Literasi: Jurnal Ilmiah Pendidikan Bahasa, Sastra Indonesia dan Daerah, 2023)
This research is motivated by instructions from the government regarding the implementation of the Profil Pelajar Pancasila. The academic community is required to integrate Pancasila student profiles with the school’s vision. The purpose of the research is to analyze the application of the vision that has been created by the school curriculum development team as an effort to realize national education goals in the era of Kurikulum Merdeka in educational units in one of the schools in the city of Bandung. This study uses a case study method with a qualitative approach. Data collection techniques through questionnaires, interviews, and observation. Subjects in this research were teachers and principals in one of elementary schools in the city of Bandung. The results of this study show that through the application of the vision, which is abbreviated as MANTAP, an acronym of Mandiri, Akhlak Mulia, Nasionalis, Tangguh, and Peduli. Students in one of the elementary schools in the city of Bandung are seen to have good implementation according to the vision contained in habit and learning. The vision implemented is following the objectivies of the independent curriculum, namely students with a Profil Pelajar Pancasila.